[RETRACTED] Current State of Scaffolding Unsafe Factor: A Thematic Review - Mohammad, Mazlina Zaira; Ja’afar, Muhd Salmizi; Samsudin, Nor Syamimi (International Journal of Sustainable Construction Engineering and Technology, 2024)
Construction industry plays a significant part in the growth of Malaysia's economy, and it is one of the country's most vital industries. Therefore, falling from a scaffolding is one of the most prevalent construction hazards. Scaffolding accidents are increased by factors such as inadequate capacity and incorrect usage of Personal Protective Equipment. Based on the previous studies, none of the researcher has reviewed scaffolding safety issues by using systematic literature review method. As a result, this review was driven to emphasize the current state of scaffolding unsafe factors in order to close this research gap. The purpose of this systematic review is to summarize the available research from 2012 to 2022 about the current state of scaffolding unsafe factors. The research used Atlas.ti 8, a keyword search, and a snowballing approach to filter for inclusion criteria from SCOPUS, Science Direct, and Web of Science. However, following the inclusion and exclusion procedure, only 29 papers were utilized to assess the final articles. A thematic assessment of these 29 papers identified initial codes identifying and categorizing them as follows: worker behavior, worker skill, site condition, design fault, insufficient equipment, management problem, and Personal Protective Equipment. The discovery is likely to enhance scaffolding safety on construction sites. For future research, other researcher can use primary method such as qualitative or quantitative method focusing on specific location to determine scaffolding unsafe factors for a particular type of scaffoldings.